2017
DOI: 10.3892/or.2017.5804
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miRNA-26b inhibits cancer proliferation of laryngeal carcinoma through autophagy by targeting ULK2 and inactivation of the PTEN/AKT pathway

Abstract: Abstract. Laryngeal carcinoma is one of the most common tumors of the head and neck cancers, the pathogenesis of which remains yet unclear. It has been discovered through research that microRNAs (miRNAs) play an important role during the genesis of laryngeal carcinoma. In the present study we investigated the effect of miRNA-26b on the proliferation of laryngeal carcinoma and elucidated the potential underlying mechanisms in order to provide new targets for laryngeal carcinoma. Firstly, we found that miRNA-26b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…It has been demonstrated that elevated Beclin‐1 expression might inhibit laryngeal cancer cells and potentially increase apoptosis 13 . Notably, it is confirmed that ATGs may be as a promising novel therapeutic target to enhance chemosensitivity 14‐16 . There is evidence that PI3K/Akt signaling pathway participates in the modulation of intracellular autophagy 17‐19 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been demonstrated that elevated Beclin‐1 expression might inhibit laryngeal cancer cells and potentially increase apoptosis 13 . Notably, it is confirmed that ATGs may be as a promising novel therapeutic target to enhance chemosensitivity 14‐16 . There is evidence that PI3K/Akt signaling pathway participates in the modulation of intracellular autophagy 17‐19 .…”
Section: Introductionmentioning
confidence: 96%
“…13 Notably, it is confirmed that ATGs may be as a promising novel therapeutic target to enhance chemosensitivity. [14][15][16] There is evidence that PI3K/ Akt signaling pathway participates in the modulation of intracellular autophagy. [17][18][19] Inhibition of PI3K/Akt signaling transduction by regulating autophagy facilitates the enhancement of the radiosensitivity of prostate cancer, glioma, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The PTEN gene can suppress tumor transcription. Moreover, it is related to tumor pathological differentiation and prognosis (26). Notably, in the present study, the promotion of MTDH or the inhibition of PTEN reduced the anticancer effects of miRNA-98 in hypopharyngeal carcinoma via the PTEN/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have con rmed that many miRNAs can affect the biological behaviors of multiple tumor tissues by regulating autophagy-related genes or pathways [23][24][25][26]. However, the role of miRNAs and autophagy in tumorigenesis have analyzed a limited number of ARGs and miRNAs in prostate cancer in most of the previous studies.…”
Section: Introductionmentioning
confidence: 99%